2011
DOI: 10.1080/02786826.2011.587036
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Raman Spectra of Engine-Emitted Particulates

Abstract: The morphology and nanostructure of soot from different engines were studied. The soot samples were collected from a 1.9 L Volkswagen light-duty diesel (LDD) engine for two different fuel types [ultralow sulfur diesel (ULSD) and B20] and six speed/load combinations, as well as from a heavy-duty engine using a pilot-ignited high-pressure direct-injection (HPDI) natural-gas combustion system for three different speed/load combinations. Transmission electron microscopy (TEM) was employed to investigate the soot m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 50 publications
6
31
1
1
Order By: Relevance
“…By imaging regions of the grid away from the stagnation point, where the distance between particles is much greater than the particle diameter, we virtually eliminate the possibility of creating artificial agglomerates on the grid. This device has been used extensively for compression-ignition engine exhaust sampling (Soewono and Rogak 2011) and is similar in principle to that used by Rogak et al (1993). In an earlier study of engine soot using the same TPS, it was found that particle projected area equivalent diameter measurements from the TPS/TEM method were within 5% of the mobility diameter (Soewono and Rogak 2011).…”
Section: Vehicles and Sampling Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…By imaging regions of the grid away from the stagnation point, where the distance between particles is much greater than the particle diameter, we virtually eliminate the possibility of creating artificial agglomerates on the grid. This device has been used extensively for compression-ignition engine exhaust sampling (Soewono and Rogak 2011) and is similar in principle to that used by Rogak et al (1993). In an earlier study of engine soot using the same TPS, it was found that particle projected area equivalent diameter measurements from the TPS/TEM method were within 5% of the mobility diameter (Soewono and Rogak 2011).…”
Section: Vehicles and Sampling Methodsmentioning
confidence: 96%
“…Few studies (of diesel or gasoline engines) have examined more than several hundred aggregates, so rare CNT/FUL might be dismissed as contamination. After finding the CNT/FUL particles in autorickshaw emissions, we reanalyzed TPS/TEM images from an earlier study of diesel and NG compression-ignition engines (Soewono and Rogak 2011). Review of 600 images from that study (which used the same sampling methods as used in the present work) yielded only 3 possible FULs with the characteristic hollow core.…”
Section: Are Autorickshaws the Only Vehicles Producing Cnt/ful?mentioning
confidence: 99%
“…The FWHMs of the D 1 and G bands, i.e., W(D 1 ) and W(G), have been used extensively in the literature to compare the graphitic structure of carbonaceous material (Wang et al 1990;Dippel et al 1999;Sadezky et al 2005;Knauer et al 2009;Soewono and Rogak 2011). Higher D 1 and G band FWHMs show higher levels of chemical heterogeneity and a lower degree of structural order (Knauer et al 2009).…”
Section: ¡1mentioning
confidence: 99%
“…Images of various aggregates of soot emitted for various loads of compression ignition engines in PC and HDD category vehicles made with the use of TEM technique [12]. Due to the standard complied by the engine, in literature we can distinguish between soot complying with Euro 2-4 [7,13,14].…”
Section: Figurementioning
confidence: 99%
“…2) and standards of emission of toxic components of exhaust gases complied by the engine [6,11,12]. The division of soot according to the last criterion is mainly ascribed to the change of generation of power systems with direct injection of fuel (change of such parameters as injection pressure, droplet size and dose division), optimization of combustion process as well as aftertreatment system (Tab.…”
Section: Influence Of Exhaust Gas Aftertreatment Systems Upon Formatimentioning
confidence: 99%